Hilirisasi Pariwisata Bangka Tengah dengan Aplikasi Bilingual Amazing Bateng - Diana Anggraeni; Bob Morison Sigalingging; Ghiri Basuki Putra (Laboratorium Rekayasa Sosial, Jurusan Sosiologi, FISIP Universitas Bangka Belitung, 2022)
The positive response to the rise of the tourism sector is reflected in the idea of creating a bilingual tourism application called Amazing BaTeng, which serves as a practical tool to introduce and sell Central Bangka tourism to the national and international sectors. Downstream tourism is processing various tourism research findings that are significantly sought to penetrate the industrial scale. The tourism sector in Central Bangka Regency has now become one of the essential elements of local commodities. It is still developing in a more advanced direction to build the regional economy while introducing Bangka Belitung culture in the national and international arenas and the presence of the Industrial Revolution 4.0. This study aims to identify how the downstream of Central Bangka tourism with the Amazing BaTeng bilingual application affects the progress of tourism and foreign language digital literacy in Central Bangka, Bangka Belitung Islands Province, in the new normal.